Monitoring and Diagnostics of Non-Thermal Plasmas in the Food Sector Using Optical Emission Spectroscopy - Sanda Pleslić; Franko Katalenić (Applied Sciences)
Non-thermal plasma technology is used in the food sector due to its many advantages such as low operating costs, fast and efficient processing at low temperatures, minimal environmental impact, and preservation of sensory and nutritional properties. In this article, the plasma was generated using a high-voltage electrical discharge (HVED) with argon at a voltage of 35 kV and a frequency of 60 Hz. Plasma monitoring and diagnostics were performed using optical emission spectroscopy (OES) to optimise the process parameters and for quality control. OES was used as a non-invasive sensor to collect useful information about the properties of the plasma and to identify excited species. The values obtained for electron temperature and electron density (up to <semantics>2.3 eV</semantics> and up to <semantics>1023 m−3</semantics>) confirmed that the generated plasma is a non-thermal plasma. Therefore, the use of OES is recommended in the daily control of food processing, as this is necessary to confirm that the processes are non-thermal and suitable for the food sector.